Effect of forest harvest on soil temperature and water storage and movement patterns on Boreal Plain hillslopes. Issue 6 (1st November 2005) - Chanasyk, D S; Prepas, E E; Whitson, I R
Abstract : Through its effect on vegetation, forest harvesting affects soil moisture storage, water movement processes, and soil temperature. The effects of harvest on water storage and movement patterns and on soil temperature during the snowmelt period were studied 3 years after harvest on hillslopes in northern Alberta, Canada. Measurements of soil water content, soil temperature, and bromide tracer concentrations were made at 11 pairs of forested and harvested plots, which are all dominated by Gray Luvisol soils but possess a range of topographic characteristics. Compared with forested sites, harvested sites were expected to have higher soil water content, display more interflow, and thaw earlier. Harvested sites were wetter on only one of four dates sampled, reflecting dry weather and rapid aspen regrowth. Greater loss and shallower penetration of bromide tracer in plots indicate that harvested sites had more interflow than forested sites. Despite a trend to higher temperatures, harvested sites did not thaw earlier than forested sites. Our inability to detect dramatic treatment effects reflects the need for large sample sizes for soil properties that display high local spatial and temporal variability.